2014
DOI: 10.1186/1471-2407-14-245
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell-free methylated DNA and lactate dehydrogenase release in colorectal cancer

Abstract: BackgroundHypermethylation of DNA is an epigenetic alteration commonly found in colorectal cancer (CRC) and can also be detected in blood samples of cancer patients. Methylation of the genes helicase-like transcription factor (HLTF) and hyperplastic polyposis 1 (HPP1) have been proposed as prognostic, and neurogenin 1 (NEUROG1) as diagnostic biomarker. However the underlying mechanisms leading to the release of these genes are unclear. This study aimed at examining the possible correlation of the presence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 52 publications
3
37
0
Order By: Relevance
“…LDH can be released during tissue damage and is involved in tumor initiation and metabolism. Numerous studies have shown that LDH activity is an indicator of metastatic risk and could be an important prognostic factor in a variety of cancers (Weide et al 2013;Cetin et al 2014;Philipp et al 2014;Ulas et al 2014;Liu et al 2015). The use of LDH as a prognostic factor in SCLC has also been demonstrated over recent decades (Tas et al 2001;Bremnes et al 2003;Hermes et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…LDH can be released during tissue damage and is involved in tumor initiation and metabolism. Numerous studies have shown that LDH activity is an indicator of metastatic risk and could be an important prognostic factor in a variety of cancers (Weide et al 2013;Cetin et al 2014;Philipp et al 2014;Ulas et al 2014;Liu et al 2015). The use of LDH as a prognostic factor in SCLC has also been demonstrated over recent decades (Tas et al 2001;Bremnes et al 2003;Hermes et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] Furthermore, several studies have suggested that elevated LDH levels are correlated with radio/chemoresistance in several malignancies. LDH is essential for anaerobic glycolysis and converts pyruvate to lactate reversibly.…”
Section: Sclcmentioning
confidence: 99%
“…HLTF promoter methylation is rarely observed in normal colon tissue (3.0-10.2 %). However, it is increased in colon adenoma (25.7-68.5 %) [13,56] and remains stable or slightly increased in invasive carcinomas (34.3-41.4 %), independently of tumor stage [13,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] ( Table 3). HLTF promoter hypermethylation was analyzed in association with the methylation of other genes.…”
Section: Hltf Silencing Through Promoter Hypermethylationmentioning
confidence: 99%
“…Several groups detected HLTF promoter hypermethylation in serum/plasma of patients with colon cancer (Table 3) [62][63][64][65][66][67][68]. The purpose of analyzing gene methylation in cancer patients is for use as a biomarker to predict outcomes, including survival and disease recurrence.…”
Section: Hltf Silencing Through Promoter Hypermethylationmentioning
confidence: 99%